Nonsurgical Procedures for Keratoconus Management - L. Rico-Del-Viejo; M. Garcia-Montero; J. L. Hernández-Verdejo; S. García-Lázaro; F. J. Gómez-Sanz; A. Lorente-Velázquez (Journal of Ophthalmology)
Objectives. To describe the past 20 years’ correction modalities for keratoconus and their visual outcomes and possible complications. Methods. A review of the published literature related to the visual outcomes and possible complications in the context of keratoconus management using nonsurgical procedures for the last 20 years (glasses and contact lenses) was performed. Original articles that reported the outcome of any correction modalities of keratoconus management were reviewed. Results. The most nonsurgical procedure used on keratoconus management is the contact lens fitting. Soft contact lenses and soft toric contact lenses, rigid gas-permeable contact lenses, piggyback contact lens system, hybrid contact lenses, and scleral and corneoscleral contact lenses form the contemporary range of available lens types for keratoconus management with contact lenses. All of them try to restore the vision, improve the quality of life, and delay surgical procedures in patients with this disease. Complications are derived from the intolerance of using contact lens, and the use of each depends on keratoconus severity. Conclusions. In the context of nonsurgical procedures, the use of contact lenses for the management of keratoconic patients represents a good alternative to restore vision and improve the quality of live in this population.